Convince Yourself to Do the Right Thing: The Effects of Provided Versus Self-Generated Arguments on Rule Compliance and Perceived Importance of Socially Desirable Behavior - Lemmen, Nieke; Keizer, Kees; Bouman, Thijs; Steg, Linda (Frontiers in Psychology, 2020)
One way to enhance rule compliance is to provide people with arguments explaining why the desired behavior is important. We argue that there might be another, potentially more effective way to enhance rule compliance: ask people to generate arguments in favor of the rule themselves, which can trigger a process of self-persuasion. We compared the effects of providing arguments, asking respondents to generate arguments themselves, and a combination of both approaches on rule compliance and the perceived importance of the rule. A field experiment revealed that rule compliance was higher in all experimental conditions compared to a control condition, with the highest level of rule compliance in the conditions that either presented the arguments or asked people to generate arguments themselves. Yet the rule was only evaluated as more important compared to the control condition, when people generated arguments themselves. This study suggests that rule compliance and perceived importance of this rule can be enhanced by easy low-cost interventions.